CD5‐positive follicular lymphoma: prognostic significance of this aberrant marker?. Issue 4 (April 2014) - Mayson, E.; Saverimuttu, J.; Cartwright, K.
Abstract Follicular lymphomas are the most common of the clinically indolent non‐Hodgkin lymphomas. The immunophenotypic pattern of follicular lymphoma classically demonstrates the B‐cell markers CD19, CD20, CD22, CD79a, surface immunoglobulin and CD10. The tumour cells are usually negative for CD5. We described two cases of CD5‐positive follicular lymphoma. This finding has rarely been described. Our aim was to discuss two cases of CD5‐positive follicular lymphoma and review the published literature on the significance of CD5 expression. Bone marrow biopsies showing involvement with follicular lymphoma at our institution over the past 34 months were evaluated for the presence of CD5 positivity by flow cytometry and immunohistochemistry. Two of eight cases (25%) of the follicular lymphomas with marrow involvement at our institution were found to be CD5‐positive. Only 36 cases of CD5‐positive follicular lymphoma have previously been described in the literature. The clinical and therapeutic significance of this remains uncertain. More research into such cases may establish whether the presence of this aberrant marker bears prognostic significance.